In-office drainage of a frontoethmoidal mucocele with non-axial proptosis: an alternative to operating-room drainage - Reuben Abraham Thomas; Shahrul Hitam; Nor Eyzawiah Hassan; Farah Dayana Zahedi (Medical Communications Sp. z o.o., 2024)
Indexed by WOS/SCOPUS